y= 2/3X-6

Help me with matthhh

WYZANT.COM
CREATE FREE ACCOUNT
Sign In

Access thousands of free resources from expert tutors

Comment on posts and interact with the authors

Ask questions and get free answers from tutors

View videos, take interactive quizzes, and more!

y= 2/3X-6

Help me with matthhh

Tutors, please sign in to answer this question.

**Solution: A = 2** Please read the following step by step solution.

STEP 1: **Read**, **understand** the situation within,
**identify** and pull out **important** information.

- y = (2/3)x - 6 it's in a slope form equation y=mx+b, where m(slope)=2/3; b(y-intercept)=-6
- The standard form equation leads to the slope form equation just by isolating "y" and by doing opposite operations.
- To transform a "slope form" into a "standard form", we just do the inverse process: the variables x, y, must be in the same side of the equation.

STEP 2: **Translate keywords** to their mathematical symbols:

- Standard form equation: Ax + By = C, where A is a positive integer, B and C integer numbers
- A = ? ; B = ? ; C = ?

STEP 3: **Set up** and **solve** the equation or problem:

y = (2/3)x - 6 Get rid of the variable x (with its coefficient) on the right side

-(2/3)x -(2/3)x

-(2/3)x + y = -6 As "A" must be positive integer, get first rid of the denominator of the fraction coefficient of "x", by multiplying the whole equation by "3"

3 * ((-2/3) (x) + y = -6) Apply the distributive property of multiplication

(3/1)*(-2/3) (x) + 3y = 3*(-6)

(3*-2)/(1*3) (x) + 3y = -18 Simplify

-2x + 3y = -18 Now get rid of the negative sign of "x" by multiplying the whole equation by -1

(-1) (-2x + 3y = -18) Apply the distributive property of multiplication

** 2x - 3y = 18** There you have the equation in standard form! **A = 2**

STEP 4: **Check** the solution:

Transform the standard form equation solution into a slope intercept form. We must get the original equation given in slope intercept form!

2x - 3y = 18 Isolate "y" by first getting rid of 2x in the left side of the equation

-2x -2x

-3y = -2x + 18 Get rid of the coefficient -3, by dividing the whole equation by -3

(-1/3) (-3y = -2x + 18) Applying the distributive property of multiplication

(3/3)y = (2/3)x + (-1/3) (18) Simplifying

**y = (2/3)x -6** We got the same original slope intercept form equation!

STEP 5: **Curiosities**

- Having the equation in "standard form" it's really easy to get the
**y-intercept point**(0,y) and the**x-intercept point**(x,0).

y-intercept: 2(0)-3y=18; -3y=18; (-3/-3)y=(18)/(-3); y=-6;

*y-intercept point (0, -6)*

x-intercept: 2x-3(0)=18; 2x=18; (2/2)x=(18)/(2); x=9;

* x-intercept point (9, 0)*

**Graphing**the equation in standard form: find the y-intercept point and x-intercept point, as we already did it. Plot them in a Cartesian plane and draw a line through both intercept points. And voila' you got it!

Standard form of a linear equations is Ax + By = C.

y = 2/3x - 6

Multiply entire equation by 3 to remove the fraction.

3y = 2x - 18

Next, subtract 2x from both sides of the equation.

-2x + 3y = -18

Now we have the equation in standard form therefore the coefficient of the x-term is -2.

Note: There are infinite standard forms.

Standard form of a linear equation is Ax+By=C, where A, B, and C are all integers. Your equation is given in slope-intercept form (usually stated as y=mx+b), so we have to isolate the constant term and then multiply through by the least common denominator of any fractions in the coefficients.

y = (2/3)x + (-6)

(-2/3)x + y = (-6)

(-2)x + 3y = (-18)

And the coefficient of x is -2.

- Algebra 2 488
- Prealgebra 37
- Geometry 261
- Math 1329
- Quadratic Formula 30
- Precalculus 102
- SAT Math 1
- Trigonometry 159
- Calculus 165
- Study Skills 6